2002
DOI: 10.1080/09613210110114028
|View full text |Cite
|
Sign up to set email alerts
|

Investment in construction and economic growth in developing countries

Abstract: Background: Cognitive Muscular TherapyTM (CMT) is an integrated behavioural intervention developed for knee osteoarthritis. CMT teaches patients to reconceptualise the condition, integrates muscle biofeedback and aims to reduce muscle overactivity, both in response to pain and during daily activities. This nested qualitative study explored patient and physiotherapist perspectives and experiences of CMT.Methods: Five physiotherapists were trained to follow a well-defined protocol and then delivered CMT to at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 6 publications
3
42
0
Order By: Relevance
“…The contribution of the construction industry required for a steady economic growth as suggested by Edmonds (1979) should be 5% of GDP. Lopes, Ruddock, and Ribeiro (2002) also demonstrated that when the share of construction value added in GDP was around 4e5%, the economy would enter a period of sustained growth. The level should be interpreted within the long-term trend rather than the annual fluctuation (Lopes et al, 2002).…”
Section: National Incomementioning
confidence: 94%
“…The contribution of the construction industry required for a steady economic growth as suggested by Edmonds (1979) should be 5% of GDP. Lopes, Ruddock, and Ribeiro (2002) also demonstrated that when the share of construction value added in GDP was around 4e5%, the economy would enter a period of sustained growth. The level should be interpreted within the long-term trend rather than the annual fluctuation (Lopes et al, 2002).…”
Section: National Incomementioning
confidence: 94%
“…In Bon's 1992 paper, the link between economic development and construction is discussed and Bon points out the problem with Turin's analysis, which is largely focused on developing countries. as the share of construction in total output first increases and then decreases with economic development, this is called the inverted U-shaped relationship, following Maddison, who, in his seminal study of economic development (Maddison, 1987), tracked several key advanced industrial countries (aICs). Bon's 1992 argument concerns the entire path from lDC (least developed countries) to nIC (newly industrialised countries) to aIC status (figures 1 and 2).…”
Section: The Role Of Construction In Economic Developmentmentioning
confidence: 99%
“…For example, Edmonds (1979) suggested that for a steady economic growth in developing countries, the contribution of the construction industry to GDP needs to be 5%. Lopes, Ruddock and Ribeiro (2002) also showed that the economy would enter a steady growth while the share of value added by the construction industry to the GDP is 4-5 %.…”
Section: Introductionmentioning
confidence: 99%